1-(12-Bromododecyl)-5-chloroindoline-2,3-dione - Zineb Tribak; Youssef Kandri Rodi; Amal Haoudi; El Mokhtar Essassi; Fréderic Capet; Hafid Zouihri (IUCrData, 2016)
In the structure of the title compound, C20H27BrClNO2, the 5-chloroindoline-2,3-dione ring system is approximately planar, the largest deviation from the mean plane being 0.0237 (10) Å. The mean plane through the fused-ring system makes a dihedral angle of 61.00 (18)° with the mean plane passing through the 1-dodecyl chain. All C atoms of the dodecyl group adopt the planar zigzag arrangement normally observed in n-alkane compounds. In the crystal, molecules are linked by C—H...O hydrogen bonds, forming chains parallel to the b axis.